Drivers and modulators in the central auditory pathways - Lee, Charles C.; Sherman, S. M. (Frontiers in Neuroscience, 2010)
The classic view of auditory information flow depicts a simple serial route from the periphery through tonotopically-organized nuclei in the brainstem, midbrain and thalamus, ascending eventually to the neocortex. Yet, complicating this picture are numerous parallel ascending and descending pathways, whose roles in auditory processing are poorly defined. To address this ambiguity, we have identified several anatomical and physiological properties that distinguish the auditory pathways into two groups that we have termed ‘drivers’ and ‘modulators’. Driver pathways are associated with information-bearing pathways, while modulator pathways modify these principal information streams. These properties illuminate the potential roles of some previously ill-defined auditory pathways, and may be extended further to categorize either unknown or mischaracterized pathways throughout the auditory system.